Seeds Viability and Initial Growth of Akasia Krasikarpa (Acacia crassicarpa A. Cunn. Ex Benth.) Seedling from Five Seed Source in Indonesia - Edje Djamhuri; Naning Yuniarti; Hanny Dwi Purwani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Plant forest development is needed for the timber industry and other industrial raw materials. Right species selection and use of seeds from good source is a success key in forest plant development. One of prospective species that can be developed in plant forest is A. crassicarpa. Seed source that have been available for A. crassicarpa such as from Seed Production Area (SPA), and Seedling Seed Orchard (SSO). Plant material quality which good can be seen from seed viability, physical quality of seedling, and early growth in field. The aim of this research is to exammine seed source effect on seed viability, seedling physic quality, and early growth of A. crassicarpa on field. Examination of seed viability used Complete Randomized Design (CRD), while examination of physical quality of seedling and initial growth on field used Complete Randomized Block Design (CRBD). Seed source was examined are Jambi SPA (AJA), Parungpanjang SPA (APJ), Riau SPA (ARA), Palembang SSO (KPL), dan Riau SSO (KRK). The result showed that seed source affected on germination seed power, seedling sturdiness, total dry weight, seedling quality index, height increment, and diameter increment. Germination power A. crassicarpa from SSO tends to higher than seed from SPA. Seedling sturdiness from A.crassicarpa seedling which from SSO was better than seed from SPA. Total dry weight and seedling quality index of A. crassicarpa that come from Parungpanjang SPA and Palembang SSO was higher than seeds from Riau SSO, Jambi SPA, and Riau SPA. Height increment and diameter increment A. crassicarpa at the age of three months old whom it’s source from SSO tends higher than seed from SPA. Seed source SSO Palembang are superior in seed viability, physical quality of seddling, and initial growth of A. crassicarpa on field.